2016
DOI: 10.1103/physreva.93.063842
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic upper bound on two-qubit polarization entanglement predetermined by pump polarization correlations in parametric down-conversion

Abstract: We study how one-particle correlations transfer to manifest as two-particle correlations in the context of parametric down-conversion (PDC), a process in which a pump photon is annihilated to produce two entangled photons. We work in the polarization degree of freedom and show that for any two-qubit generation process that is both trace-preserving and entropy-nondecreasing the concurrence C(ρ) of the generated two-qubit state ρ follows an intrinsic upper bound with C(ρ) ≤ (1+P )/2, where P is the degree of pol… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 46 publications
2
11
0
Order By: Relevance
“…Finally, we have shown that the concurrence of time-energy entangled two-qubit states is bounded by the degree of temporal coherence of the pump field. This result extends previously obtained results in the spatial [19] and polarization [31] degrees of freedom to the temporal degree of freedom and can thus have important implications for understanding how correlations of the pump field in general manifest as twoparticle entanglement. Our results can also be important for time-energy two-qubit based quantum communication applications.…”
Section: Conclusion and Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Finally, we have shown that the concurrence of time-energy entangled two-qubit states is bounded by the degree of temporal coherence of the pump field. This result extends previously obtained results in the spatial [19] and polarization [31] degrees of freedom to the temporal degree of freedom and can thus have important implications for understanding how correlations of the pump field in general manifest as twoparticle entanglement. Our results can also be important for time-energy two-qubit based quantum communication applications.…”
Section: Conclusion and Discussionsupporting
confidence: 88%
“…We note that in situations in whichγ d (∆τ ′ ) ≈ 1 and κ 1 = κ 2 , the maximum achievable concurrence for a pulsed field can be unity in principle and for a continuous-wave field it can be unity as long as ∆τ is much smaller than the coherence time of the pump field. The above result is the temporal analog of the results obtained in the polarization [31] and spatial [19] degrees of freedom. However, unlike in the spatial degree of freedom, which does not involve any space-averaged detection scheme, the results derived in this article show that even for the time-averaged detection schemes, the temporal correlation properties of the pump do directly decide the upper limit on entanglement that a time-energy entangled two-qubit state can achieve.…”
Section: Rsupporting
confidence: 75%
See 1 more Smart Citation
“…One such example is the two-qubit state generator proposed in Ref. [40] using four PDC cyrstals. In Fig.…”
Section: Measuring the Intrinsic Degree Of Coher-ence Of Two-qubit Stmentioning
confidence: 99%
“…In recent years, transfer of the coherence properties of the pump photon to the signal and idler photons has been studied in various different contexts [40,45,46]. In this section, we investigate this transfer in terms of the intrinsic degree of coherence.…”
Section: Transfer Of Intrinsic Degree Of Coherence In Pdcmentioning
confidence: 99%